1-Dimensional confinement of porous polyethylenedioxythiophene using carbon nanofibers as a solid template: an efficient charge storage material with improved capacitance retention and cycle stability - Anothumakkool, Bihag; Bhange, Siddheshwar N.; Unni, SreeKuttan M.; Kurungot, Sreekumar (RSC Advances, 2013)
Here, we report a highly conducting porous 1-dimensionally (1-D) confined nano hybrid of polyethylenedioxythiophene (PEDOT) using a cup-stacked hollow carbon nanofiber (CNF) as a solid template for potential charge storage applications. The unique features of the nano confinement involve significantly high porosity and conductivity with the establishment of the 1-D architecture. Since the tubular morphology of the CNF with its open tips provides facile routes for the electrolyte, the overall utilization of the active surface and conductivity increases the charge storage properties of PEDOT in the hybrid. The approach helped in achieving a high specific capacitance of 177 F g(-1) for 40% PEDOT-CNF at a scan rate of 50 mV s(-1) and in retaining 130 F g(-1) even at 3000 mV s(-1) compared to 76 and 30 F g(-1) respectively given by pure PEDOT in 0.5 M H2SO4. The hybrid CP-40 shows a very high power density of 51 kW kg(-1) with an energy density of 4.7 Wh kg(-1). High capacitance retention is supported by the low charge transfer resistance and very low time constant (less than 0.5 s) values for the hybrid using impedance analysis. Phase angle calculations from a Bode plot also show an ideal capacitive nature with -90 degrees phase difference at 0.1 Hz for the hybrids. Apart from all these, the solid CNF backbone helps the hybrid material to display excellent cycle stability with >98% retention in capacitance over 4500 charge-discharge cycles compared to pristine PEDOT at a current density of 2 A g(-1).